2012
DOI: 10.1111/j.1741-6787.2012.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Icelandic Nurses' Beliefs, Skills, and Resources Associated with Evidence‐Based Practice and Related Factors: A National Survey

Abstract: Icelandic RNs' beliefs regarding EBP are similar to those of RNs in other countries. Their access to EBP resources is generally good, but they lack the skills and knowledge needed for EBP. Strategies aimed at changing the organizational and practice context need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
91
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(115 citation statements)
references
References 41 publications
(69 reference statements)
12
91
0
12
Order By: Relevance
“…Although EBP has gained considerable attention in research and literature, evidence attests that nurses have not been successful to employ EBP in their profession . A number of factors are recognised to be associated with the use of EBP in nursing (such as issues related to time, value for research, lack of organisational support and searching skills) among which are factors related to searching skills of electronic bibliographic databases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EBP has gained considerable attention in research and literature, evidence attests that nurses have not been successful to employ EBP in their profession . A number of factors are recognised to be associated with the use of EBP in nursing (such as issues related to time, value for research, lack of organisational support and searching skills) among which are factors related to searching skills of electronic bibliographic databases …”
Section: Introductionmentioning
confidence: 99%
“…Prior research demonstrated that nurses’ use of electronic evidence has remained limited and they mostly prefer to ask for information from their health care colleagues rather than peer reviewed publications available in pertinent online databases . Surveys such as that conducted by Pravikoff et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nurses' beliefs and attitudes correlate with the extent of EBP implementation (Bostr€ om et al 2013;Melnyk et al 2008bMelnyk et al , 2010bSquires et al 2011;Stokke et al 2014;Thorsteinsson 2013;Wilson et al 2015;Yoder et al 2014). Finally, convictions on EBP are more positive in those who receive training in evidence-based care (Melnyk et al 2008b;Stokke et al 2014;Thorsteinsson 2013;Wilson et al 2015;Yoder et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Nurses in clinical practice report that their educational preparation for accessing and using EBP is insufficient (Oh et al, 2010, p. 387). Research has shown that despite the fact that nurses are convinced about the importance of EBP, its implementation into practice tends to be problematic (Boström et al, 2013;Stokke et al, 2014;Thorsteinsson, 2013). This is one of the reasons why educational institutions are increasingly interested in incorporating EBP issues into the nursing and midwifery curricula.…”
Section: Introductionmentioning
confidence: 99%